Acute Postoperative Pulmonary Embolism Detected at Home by a Patient's Personal Activity Monitor: A Case Report. Issue 2 (April 2021) - Drynan, David; Leroux, Timothy S.; Zywiel, Michael G.
Abstract : Case: The increase in smart technology and integration into health care is inevitable. We present a case of a smart wristwatch prompting a patient readmission to the emergency department for postoperative pulmonary embolism investigation and management. This prompted the assessment for community-based smart technology use and integration to the postoperative monitoring and the associated issues. Conclusion: Community-based smart technology is here to stay and is developing at a staggering rate, specifically with the cross-over to health monitoring. Constant patient monitoring and alerts are advantages, with smart technology and medical attention in this case. Surrounding issues of the technology must be considered with implementation.